2014
DOI: 10.5194/nhess-14-1579-2014
|View full text |Cite
|
Sign up to set email alerts
|

Projecting flood hazard under climate change: an alternative approach to model chains

Abstract: Abstract. Flood hazard projections under climate change are typically derived by applying model chains consisting of the following elements: "emission scenario -global climate model -downscaling, possibly including bias correctionhydrological model -flood frequency analysis". To date, this approach yields very uncertain results, due to the difficulties of global and regional climate models to represent precipitation. The implementation of such model chains requires major efforts, and their complexity is high.W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Climate indices (e.g. Delgado et al, 2014;Salas and Obeysekera, 2014) and extreme precipitation (e.g. Prosdocimi et al, 2014;Villarini et al, 2009) are more common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate indices (e.g. Delgado et al, 2014;Salas and Obeysekera, 2014) and extreme precipitation (e.g. Prosdocimi et al, 2014;Villarini et al, 2009) are more common.…”
Section: Discussionmentioning
confidence: 99%
“…Wilby and Quinn, 2013). Delgado et al (2014) modelled the scale parameter of a log-normal distribution as a function of the non-stationary standard deviation of an atmospheric circulation index representing Western Pacific monsoon activity. By evaluating a deviance statistic based on the log-likelihood of the parameter fit they found the non-stationary model to be a significant improvement over the stationary model for their case of the lower Mekong flood series.…”
Section: Introductionmentioning
confidence: 99%
“…Delgado et al (2010Delgado et al ( , 2012Delgado et al ( , 2014 explore this avenue for the Lower Mekong River. They found that average floods have slightly decreased during the last few decades, but that the variability of the annual maximum floods has increased significantly.…”
Section: Low-dimensional Change Models For Flood Changesmentioning
confidence: 99%
“…For river gauges in the Mekong Basin, Delgado et al (2012) identify a statistical relationship between flood variance and the western Pacific monsoon variance. A non-stationary flood frequency model is developed in which the monsoon variance drives temporal changes in flood quantiles (Delgado et al, 2014). For climate change scenarios, the variance of the monsoon is extracted from GCM runs.…”
Section: Climate Change: Model Chain Versus Model-chainaugmented?mentioning
confidence: 99%